Efficacy of RNA polymerase II inhibitors in targeting dormant leukaemia cells - Pallis, Monica; Burrows, Francis; Whittall, Abigail; Boddy, Nicholas; Seedhouse, Claire; Russell, Nigel (BioMed Central, 2013)
Background Dormant cells are characterised by low RNA synthesis. In contrast, cancer cells can be addicted to high RNA synthesis, including synthesis of survival molecules. We hypothesised that dormant cancer cells, already low in RNA, might be sensitive to apoptosis induced by RNA Polymerase II (RP2) inhibitors that further reduce RNA synthesis.